PENGARUH POLA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI SD NEGERI 6 MANDAU - Septina Katrin (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The problem discussed in this study is the pattern of school leadership leadership on teacher performance in SD Negeri 6 Mandau. The purpose of this study was to determine whether there is an influence of the principal's leadership pattern on the performance of teachers in SD 6 Mandau. The design of this study uses a quantitative approach. This study is ex-post facto because in this study only presents data on events that have taken place and have been available to respondents without providing treatment or manipulation of the variables studied. The results showed that the headmaster's leadership evaluation by the teacher in this study was in the high category of 57.1% (8 teachers) and in the medium category was 42.9% (6 teachers). Assessment of teacher performance, the results of this assessment are in the high category of 64.3% (9 teachers) and in the moderate category of 35.7% (5 teachers). while testing the hypothesis in this study is the principal's leadership significantly influence the performance of Mandau 6 Elementary School teachers, based on the results of Ha's research received and Ho rejected. This is indicated by the significance value in the regression test that is smaller than the significance level, which is <0.05 and the Fcount value greater than Ftable is 64.333> 4.20. Based on the results of this study, researchers can conclude that the principal's leadership pattern influences the performance of teachers in SD 6 Mandau